2014
DOI: 10.1111/pcn.12206
|View full text |Cite
|
Sign up to set email alerts
|

Information processing during sleep and stress‐related sleep vulnerability

Abstract: Aims: Previous studies showed enhanced attention and decreased inhibitory processes during early nonrapid eye movement sleep in primary insomnia patients, as measured by event-related potentials. The current study aims to examine information processing during sleep in non-insomniac individuals with high vulnerability (HV) to stress-related sleep disturbances.Methods: Twenty-seven non-insomniac individuals were recruited, 14 with low vulnerability and 13 with HV. After passing a screening interview and polysomn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The FIRST has been widely used in previous research (Drake, Scofield, & Roth, 2008; Drake et al, 2011; Yang, Chou, & Hsiao, 2011; Lin, Jen, & Yang, 2014), and has demonstrated good psychometric properties. Furthermore, previous studies have reported a significant correlation between FIRST scores and polysomnographic measures of sleep, as well as latencies on the Multiple Sleep Latency Test (Drake et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FIRST has been widely used in previous research (Drake, Scofield, & Roth, 2008; Drake et al, 2011; Yang, Chou, & Hsiao, 2011; Lin, Jen, & Yang, 2014), and has demonstrated good psychometric properties. Furthermore, previous studies have reported a significant correlation between FIRST scores and polysomnographic measures of sleep, as well as latencies on the Multiple Sleep Latency Test (Drake et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The Ford Insomnia Response to Stress Test (FIRST; Drake et al, 2004) is a 9-item questionnaire (4-point Likert scale) assessing vulnerability to stress-related sleep disturbances (i.e., sleep reactivity). The FIRST has been widely used in previous research (Drake, Scofield, & Roth, 2008; Drake et al, 2011; Yang, Chou, & Hsiao, 2011; Lin, Jen, & Yang, 2014), and has demonstrated good psychometric properties. Furthermore, previous studies have reported a significant correlation between FIRST scores and polysomnographic measures of sleep, as well as latencies on the Multiple Sleep Latency Test (Drake et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Nakajima et al (2014) found that insomnia patients scored higher in FIRST than a group of healthy controls. Another study used the FIRST to examine information processing during sleep in a non-insomniac sample with high vulnerability to stress-related sleep disturbances (Lin, Jen and Yang, 2014). Vargas, Friedman and Drake (2015), in a sample of community participants, observed that sleep reactivity was associated with greater depressive symptoms, and this link was partially mediated by insomnia.…”
Section: Introductionmentioning
confidence: 99%